Effect of firing temperature to surface morphology of nanosized YIG based thick film with linseed oil as organic vehicle - Hasan, Intan Helina; Hamidon, Mohd Nizar; Mohd Kusaimi, Muhammad Asnawi; Azhari, Saman; Mohd Azhari, Nur Alin; Osman, Rosiah; Md Yusof, Juraina; Ismail, Ismayadi (2018)
This paper presents results of morphological study on nanosized yttrium iron garnet (YIG) thick film using linseed oil as organic vehicle and nanosized YIG powder. First, YIG nanopowder is mixed with organic vehicle which consists of linseed oil, m-xylene and α-terpineol. Paste samples were screen printed onto alumina as substrate, dried and fired at different temperatures of 100°C, 200°C, and 300°C respectively. Microscopic images of the samples and elemental analysis were observed to determine good dispersion of the active powder with the organic vehicle. Based on the results, the nanoparticles were uniformly dispersed, with images of thick films fired at 200°C and 300°C have showed clearly visible particles, indicating that at these temperatures, the organic vehicle has started to evaporate on the surface, revealing nanoparticles of the active powders. Elemental analysis confirmed this theory, of which carbon element of the organic vehicle gradually decreased with increasing temperature.